Advancements in surface-enhanced femtosecond stimulated Raman spectroscopy: exploring factors influencing detectability and shapes of spectra - Pyrcz Patryk; Gawinkowski Sylwester (Nanophotonics)
A combination of femtosecond stimulated Raman scattering and surface-enhanced Raman scattering, termed surface-enhanced stimulated Raman scattering (SE-FSRS), was proposed to leverage both temporal precision and sensitivity for advanced molecular dynamics analysis. During the initial successful implementations of this approach, unexpected spectral distortions were observed, and several potential explanations were proposed. Further progress in this novel technique and its broader implementation requires a profound understanding of the factors influencing the shape of the registered spectra and the underlying mechanisms. Here we present findings on how pulse energy and excitation wavelengths affect SE-FSRS spectra, emphasizing the influence of a strong broadband background on spectral dispersion. These insights contribute to understanding the complex mechanisms underlying SE-FSRS and suggest methods to improve the control and application of this spectroscopic technique, highlighting its potential to provide deeper insights into molecular dynamics. This work represents a significant step toward exploiting SE-FSRS for advanced analytical applications.